MENINGKATKAN KETERLIBATAN ORANG TUA DALAM KEGIATAN SEKOLAH DI MADRASAH ALIYAH - Deny Ahmad Jaelani; Sherin Sanitari; Mahsunul Aripin Mardatilah; Aulia Rahma; Salma Vasya Aulia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to develop a comprehensive strategy and model to enhance students’ active participation in school activities at Madrasah Aliyah through a literature-based qualitative approach. Low student participation and limited parental involvement in madrasah programs remain key challenges that hinder character development and academic achievement. Several internal and external inhibiting factors, such as low interest and motivation, weak parental support, limited learning resources, heavy academic workload, and inadequate access to technology, are systematically analyzed. The article further elaborates on forms of parental involvement relevant to Islamic education, including emotional support, academic supervision, and participation in religious and collaborative class activities. In addition, a school–family partnership model based on communication and technology is proposed, which leverages digital platforms to reduce barriers of time and distance and strengthen synergy between the madrasah and the family. It is expected that this model will promote more inclusive, sustainable, and impactful involvement in improving the quality of Islamic education in Madrasah Aliyah.